Antibacterial Effects of Manalagi Apple Peel Extract Mouthwash - Emini Emini; Erwin Erwin; Rini Widiyastuti; Yusmaniar Yusmaniar (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2023)
Streptococcus mutans is a bacteria that causes dental caries, so it is necessary to intervene with preventive products such as mouthwash that has the antibacterial ability. The development of mouthwash can be done by adding active substances derived from local plant materials to increase the ability of the product, one of which is manalagi apple peel. Apples contain several substances that are known to have good benefits for dental and oral health. This situation has become the basis for researchers to develop health products, namely mouthwash or mouthwash. The purpose of this study was to determine the anti-bacterial effect of the apple peel extract mouthwash formulation against Streptococcus mutans. This type of research is experimental research. The study design was Completely Randomized Design (CRD). The mouthwash tested in this study consisted of mouthwash A (negative control: mouthwash without extract), mouthwash B (12.5% extract), mouthwash C (25% extract), and mouthwash D (50% extract). ) and mouthwash E (positive control: one of the mouthwash products from the market). The results showed that the average inhibition was M(A) 8 mm, M(B) 8 mm, M(C) 14.67 mm, M(D) 13.27, and M(D) 8 mm. The results of the analysis of the difference in antibacterial ability between mouthwashes showed a value of -value = 0.008 0.05. The study concluded that there was a significant difference in the antibacterial ability of S. mutans between mouthwash A, B, C, D, and E.